Effects of post drill specification, preparation depth and adjacent tooth status on the scanning trueness of post space: an in vitro study - Ke Huang; Jun-bin Zou; Yue-ran Guo; Hui-cong Zhu; Xiao Li (BMC Oral Health, 2026)
Abstract Background The indication for direct intraoral scanning of post spaces should be guided by the post drill. This study evaluated the influence of drill specifications, preparation depth, and the presence or absence of bilateral adjacent teeth on the scanning trueness of post spaces using two intraoral scanners (IOSs) in vitro. Methods A standard maxillary denture model was scanned for virtual post spaces preparation of the right maxillary central incisor. There were two groups of models, 8 models per group: one group with the presence of bilateral adjacent teeth and the other group with the absence of bilateral adjacent teeth. Moreover, the upper right central incisor in the 8 models in each group underwent digital post space preparation, which was designed based on the three-dimensional (3D) measurements of four drills (3 M RelyX Fiber Post sizes 2 and 3; RTD Macro-Lock #4 and #6) and prepared at depths of 8 and 10 mm. In total, 16 models were fabricated using a high-precision 3D printer. Each model was scanned 10 times with two intraoral scanners(IOSs): Shape Trios 5 and Primescan Connect; The scanned data were exported as test files, with the design data serving as the reference. Following best-fit alignment, the root mean square error (RMSE) and recognizable depth were computed. Overall group comparisons were performed with the Kruskal‑Wallis H test. Subgroup pairwise comparisons utilized the Mann‑Whitney U test and Bonferroni‑corrected Dunn’s post‑hoc test, with two‑sided α = 0.05. Results For the Trios 5 scanner, the median trueness ranged from 51.5 to 927.5 μm. The median recognizable depth varied from 4.48 to 7.98 mm in the 8 mm preparation group and from 4.45 to 9.94 mm in the 10 mm preparation group. For the Primescan scanner, the median trueness of all groups ranged from 38.0 to 88.5 μm. The median recognizable depth was 7.95 to 7.98 mm in the 8 mm group and 9.92 to 9.95 mm in the 10 mm group. Conclusions Primescan identified post spaces prepared by all 4 drills at depths ≤ 10 mm, regardless of adjacent teeth obstruction. In the presence of adjacent teeth obstruction, the Trios 5 scanner detected only the Macro‑Lock #6 preparations at ≤8 mm depth. In the absence of adjacent teeth obstruction, it further detected RelyX Size 3 and Macro‑Lock #4 preparations at depths ≤8 mm, while Macro‑Lock #6 preparations were detected at depths ≤10 mm.